Aggressive Papillary Thyroid Carcinoma Presenting with Metastasis to the Pancreas. (20th January 2022) - Warda, Firas; Ho, Sam; Kuo, Enoch; Rao, Dinesh; Jurado-Flores, Marilu
Abstract : Papillary thyroid cancer is the most common type of thyroid cancer. Aggressive forms tend to metastasize to the lungs and bones, but the abdomen is a rare site of metastasis. We present a 46-year-old male patient who presented with a neck mass associated with shortness of breath and hemoptysis. He was found to have a large thyroid mass on imaging. He underwent a total thyroidectomy with bilateral neck dissection, with pathology showing a multifocal tall cell variant of papillary thyroid carcinoma with lymphovascular invasion in both thyroid lobes. Due to recurrent findings of residual thyroid tissue on whole-body scan imaging, the patient underwent radioactive iodine ablation therapy twice, with poor response to therapy, suggested by persistently elevated thyroglobulin levels. However, the residual tissue responded to external beam radiation. After the initial response to radiation, thyroglobulin was noted to have increased again, prompting a PET-CT after administration of recombinant TSH. PET showed a focal area of increased uptake in the head of the pancreas. The patient underwent the Whipple procedure for resection of the metastasis. Pathology showed papillary thyroid carcinoma with strong and diffuse staining for TTF-1 and thyroglobulin. The patient was started on lenvatinib in the postoperative period and is currently tolerating treatment well with evidence of decreasing thyroglobulin levels. Intra-abdominal metastasis from a thyroid malignancy source is quite rare and can be challenging as far as diagnosis and treatment. Surgical resection can be curative and can be followed by radioactive iodine ablation therapy if cancer cells show avidity. Tyrosine kinase inhibitors can be used in refractory disease. New research is being conducted on new agents that can reverse the resistance to radioactive iodine therapy.